Air-Coupled Impact Echo Test with Acoustic Shield - Syakira Jamil, Aina; Abd Rahman, Norinah; Hamid, Roszilah (International Journal of Engineering and Technology, 2019)
The ability of air-coupled impact-echo technique to retrieve data in a short time is the main advantage of this technique. However, there are some external factors, especially noise disruptions arising from surrounding sound where the test is performed causing some error to the data collected. Therefore, the use of acoustic shield is introduced. This paper presents the performance of air-coupled impact echo testing in detecting concrete flaws depth and effects of different acoustic shields on the estimated flaws depth. Testing is performed on concrete slab designed to have four defects at different depth and size. Acoustic shield are made from egg crate foam, aluminium sheet, polyvinyl chloride (PVC) pipe and polypropylene (PP) plastic. Recorded data in time domain is transformed to frequency spectrum by fast Fourier transform (FFT) to obtain the peak frequency for each defect zone. Estimated depth error obtained without acoustic shield is 10.0%. The value was higher compared to the use of acoustic shield from egg crate foam, aluminium sheet, PVC pipe and PP plastic with 3.3%, 3.3%, 8.3% and 3.3% error respectively. Data analysis shows that the use of acoustic shield has reducing the effects of noise and other acoustic waves measured by error percentage. The use of egg crate foam as an acoustic shield is the most effective shield followed by aluminium sheet, PP plastic and PVC pipes.Â Â